2002
DOI: 10.1152/ajpheart.00256.2001
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin stress-response in cardiomyocytes: NF-κB activation and tumor necrosis factor-α expression

Abstract: Although tumor necrosis factor (TNF)-α is implicated in numerous cardiac pathologies, the intracellular events leading to its production by heart cells are largely unknown. The goal of the present study was to identify the role of the transcription factor nuclear factor (NF)-κB in this process. Among the many inducers of TNF-α expression in myeloid cells, only lipopolysaccharide (LPS) led to its induction in cultured neonatal myocytes. LPS also activated the NF-κB pathway, as evidenced by the degradation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 38 publications
2
52
0
Order By: Relevance
“…Over production of TNF-α and LPS stimulation may induce the activity of NF-κB and exert harmful effects on myocardial cells (35). The current results revealed that sitagliptin is able to reduce LPS-induced TNF-α production and inhibit the nuclear translocation of NF-κB.…”
Section: A B Cmentioning
confidence: 53%
“…Over production of TNF-α and LPS stimulation may induce the activity of NF-κB and exert harmful effects on myocardial cells (35). The current results revealed that sitagliptin is able to reduce LPS-induced TNF-α production and inhibit the nuclear translocation of NF-κB.…”
Section: A B Cmentioning
confidence: 53%
“…The exact mechanisms of this LPS-induced IL-6 production in myocytes remain to be defined, although there are several possible pathways that have already been proposed. These include activation of signalling pathways through activation of the Toll-like receptors (Gallaci et al, 1998) and production of NF-κB transcriptional factor (Wright et al, 2002) and reactive oxygen species (Shang et al, 2006), all of which can increase the production and secretion of IL-6 and other cytokines like TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Myocyte Cultures-Primary neonatal cardiomyocytes were isolated from 1-to 2-day-old CD-1 mouse pups using a previously described (14) method that produces cultures that exhibit spontaneous beating and Ͼ95% myocyte purity. Cells were plated on gelatin-coated plates at a density of 2 ϫ 10 6 cells per 60 mm diameter culture dish, in DMEM/F12 medium supplemented with 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%